Plasma Menthol Glucuronide as a Biomarker for the Behavioral Effects of Menthol and Nicotine in Humans - Gueorguieva, Ralitza; Schwartz, Elizabeth K. C.; MacLean, R. Ross; DeVito, Elise E.; Eid, Tore; Wu, Ran; O’Malley, Stephanie S.; Sofuoglu, Mehmet (Frontiers in Pharmacology, 2022)
This secondary analysis sought to determine if plasma menthol glucuronide (MG) concentrations predict changes in three outcomes: subjective drug effects, urges to smoke and heart rate, following concurrent inhaled menthol and intravenous nicotine. A total of 45 menthol and non-menthol cigarettes smokers (36 male, 9 female, 20 Black, and 24 White) were included in this double-blind, placebo-controlled study. Across 3 test sessions, participants were assigned to a different flavor condition for each session: 0% (no menthol), 0.5%, or 3.2% menthol. In each test session, participants received in random order one intravenous delivery of saline, and two intravenous deliveries of nicotine (0.25 mg/70 kg and 0.5 mg/70kg), each one hour apart, concurrent with menthol delivery by e-cigarettes. The main outcomes were subjective drug effects, urges to smoke, and heart rate. The results showed that following e-cigarette inhalation, plasma MG levels or “menthol boost” increased proportional to the menthol concentration in the e-liquids. While plasma MG concentrations were not predictive of increases in heart rate or subjective drug effects, which are reflective of acute effects from nicotine, they were predictive of cooling effect, a typical effect of menthol, but only in menthol smokers in the absence of concurrent active nicotine infusion. These findings demonstrate the utility of plasma MG as a biomarker both for acute menthol exposure by e-cigarette inhalation and to examine the dose-dependent behavioral and physiological effects of menthol in humans.